Criminal Law Formulation Policy for Self-abuse of Narcotics as an Effort to Prevent Prison Overcrowding - Efendi, Putri Rahma; Wijayanto, Indung (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This article will discuss the criminal law formulation policy related to self-abuse of narcotics in the present and future.Purposes of the Research: This article aims to evaluate the application of the health approach to drug abuse treatment under positive law, identify obstacles to implementation, and provide recommendations for regulatory reform to optimize the handling of these cases and reduce overcrowding in correctional institutions.Methods of the Research: The type of research used in this study is normative juridical research or normative legal research using a statutory approach (statue approach) and a comparative approach (comparative approach). The statutory approach is carried out by examining Law Number 35 of 2009 concerning Narcotics, SEMA Number 4 of 2010, and Regulation of the Attorney General Number PER-29/A/JA/12/2015. Meanwhile, the comparative approach is carried out by comparing regulations governing the abuse of narcotics for oneself in countries that have similar legal systems to Indonesia, namely Madagascar, Mexico, and Portugal. The data used is obtained from secondary data sourced from library materials such as official documents, books, research results in the form of reports, and documents relating to self-abuse of narcotics.Findings of the Research: This study found that the policy on narcotics abuse for oneself based on positive law currently uses a health approach, but in its enforcement it is still not optimally implemented. There are still many law enforcement officials who have the understanding that the criminal act of narcotics abuse for oneself is a crime that must be subject to imprisonment. This is what makes prisons in Indonesia overcrowded because most of them are inhabited by prisoners of narcotics crimes. This study recommends the need to reform future regulations regarding the abuse of narcotics for oneself as an effort to prevent prison overcrowding.